Analisis Rekonsiliasi Fiskal terhadap Perhitungan Pajak Penghasilan pada PT Dwi Putra Karya Sukses - Nadiva Nasya Rukmananda B; Cris Kuntadi; Maidani Maidani (Jurnal Mutiara Ilmu Akuntansi, 2024)
In the Astra International company, there is a reconciliation phenomenon in the asset depreciation section where there are different depreciation methods for commercial financial statements compared to fiscal financial statements research objectives: 1. To find out the calculation of Fiscal Reconciliation at PT Dwiputra Karya Sukses 2. To find out the calculation of taxes payable at PT Dwiputra Karya Sukses 3. To find out the calculation of the comparison of commercial profit and fiscal profit The type of research method used by the author is descriptive qualitative method. According to Bogdan and Biklen in Sugiyono (2020: 7) descriptive qualitative research methods are data collection in the form of words or pictures, so they do not emphasize numbers. By doing the right Fiscal Reconciliation, PT Dwiputra Karya Sukses can see the comparison between Taxable Income (PKP), namely before making a fiscal correction of Rp. 52,777,780 and after Fiscal Correction of Rp. 52,607,673. the difference in Taxable Income (PKP) also results in differences in Income Tax Payable that will be paid. The amount of income tax before fiscal correction is Rp. 5,808,555 and the amount of income tax after fiscal correction is Rp. 4,665,952. There is a difference in income tax payable of Rp. 1,142,603. Fiscal reconciliation of commercial financial statements is closely related to each other. Because it starts from revenue and expenses to the preparation of fiscal profit and loss and ends in income tax that must be paid by the company.